Parallel filtering scheme for fast symmetrical component extraction based on asynchronous coordinate transformation - Hao, Tianqu; Han, Shunxing; Yan, Guoan (Frontiers in Energy Research, 2023)
The common shortage of the existing methods for extracting symmetrical components from unbalanced and distorted three-phase voltages is that they introduce significant time delay before reaching accurate result. Therefore, this paper presents a new filtering method to fast extract the positive sequence component based on asynchronous coordinate transformation. Unlike the conventional methods who filter out the harmonics in sequence, resulting in cascaded delay time, the proposed method has two signal streams operating parallelly, which in particular refer to the negative sequence component extraction and harmonic filtering, respectively, and then the positive sequence component can be easily derived by skillfully combining the results of two signal streams. In theory, the proposed method only suffers the largest delay introduced by these two streams. By carefully designing the asynchronous coordinate transformation, the delay can be restricted thus improving the overall performance. Simulation and experimental results verified the performance of the proposed method.